НЕКОТОРЫЕ ВОПРОСЫ СОПОСТАВИТЕЛЬНОГО ИЗУЧЕНИЕ АДЪЕКТИВНЫХ ФРАЗЕОЛОГИЧЕСКИХ ЕДИНИЦ (на материалах английского и каракалпакского языков) - Сапаров, С.П. (SCIENCE and SOCIETY, 2021)
In the given article we mentioned a question about comparative research of adjectival phraseological units in English and Karakalpak languages. Such researches present a new direction within investigations of this kind, as in the modern linguistics there have been introduced a very few works done in the comparison of English and Karakalpak languages.